IMPLEMENTATION OF DIGITAL MARKETING STRATEGY TO INCREASE PROMOTION IN SOCIAL MEDIA FOR MICRO, SMALL AND MEDIUM ENTERPRISES IN DUBAI (International Conference on Social and Islamic Studies, 2022)
Social media is a great place to promote products to consumers. Social media allows market participants to communicate with each other, customers and potential customers. Social media gives identity to the brand or brands being marketed and helps to spread the message in a relaxed and communicative way. Digital marketing communication strategy is a brand promotion activity that has been planned and arranged systematically. In this study using a qualitative method which is an approach to explore and understand an event. Social Media Marketing is one of the most popular marketing techniques adopted by almost everyone to reach a wide audience in no time. But how effectively handle this platform is very important, because only sharing business-related images or videos on social media pages may not bring in customers. It is necessary to find an experienced social media marketing agency in Dubai who can help even startups get a boost through effective social media campaigns. It can be concluded that in order to expand today's business must have access to more information than ever before, while running a business, it is very important to understand all the strategies that need to be followed and need to change the strategy and increase more customers. need to find an experienced social media marketing agency in Dubai who can help even startups get a boost through effective social media campaigns.